LOW DENSITY LIPOPROTEIN CHOLESTEROL LEVEL, PULSE PRESSURE AND URIC ACID ARE ASSOCIATED WITH CAROTID INTIMA-MEDIA THICKNESS IN JAPANESE GENERAL POPULATION. (June 2018) - Fukui, A.; Mure, K.; Shimabukuro, M.; Miyai, N.; Utsumi, M.; Uematsu, Y.; Takeshita, T.; Shiba, M.; Arita, M.
Abstract : Objective: To clarify the association of triglyceride (TG), high- and low- density lipoprotein cholesterols (HDL-C and LDL-C), blood pressure, insulin sensitivity, uric acid (UA), high sensitive C-reactive protein (hsCRP), and urine albumin-to-creatinine (UACR) with carotid intima-media thickness (cIMT), which has been reported as a potential surrogate marker of early atherosclerosis, in the Japanese general populations. Design and method: A total of 2, 645 participants including 1, 205 men (61.1 ± 9.9 years) and 1, 440 women (61.2 ± 9.4 years) were enrolled in the present cross-sectional study. Systolic and diastolic blood pressure (SBP, DBP) were measured to obtain pulse pressure (PP). Fasting plasma glucose (FPG) and insulin were measured to calculate HOMA-IR. cIMT was measured by B-mode ultrasound machine (GM-72P00A, Panasonic, Kanagawa). Stepwise multiple regression analyses were performed in two models. Model 1 was adjusted for age, BMI, current smoking status, exercise habit, habitual alcohol consumption, and medication for hypertension, diabetes mellitus and dyslipidemia, including all indices shown above. The association of UA, hsCRP, UACR and HOMA-IR with cIMT was analyzed in model 2 adjusted for same variables in model 1 except PP, TG and cholesterol levels. Results: : Mean ± SD of cIMT, HDL-C, LDL-C, SBP, DBP, PP and UA were 0.68 ± 0.16 (mm), 59.1 ± 15.6 (mg/dL), 118.9 ± 30.4 (mg/dL), 131.2 ± 17.1 (mmHg), 77.3 ± 10.0 (mmHg), 54.0 ± 12.2 (mmHg) and 5.8 ± 1.8 (mg/dL), respectively, in men, and 0.63 ± 0.12 (mm), 68.3 ± 15.4 (mg/L), 127.0 ± 30.6 (mg/dL), 125.4 ± 18.1 (mmHg), 72.9 ± 10.0 (mmHg), 52.5 ± 12.5 (mmHg) and 4.3 ± 1.3 (mg/dL), respectively, in women. In model 1, LDL-C and PP were significantly associated with cIMT in men and women (P < 0.001). In men, UA also showed significant association (P = 0.002), whereas HDL-C showed significant inverse association (P = 0.001). In model 2, UA showed significant association with cIMT in men and women (P = 0.007, P = 0.002). Conclusions: : In conclusion, our results indicate the following. First, LDL-C and PP may be potential surrogate markers of early carotid atherosclerosis in both sex. Second, in men, HDL- C and UA may be important risk of it.